Inductive Helical Stent for Wireless Revascularization: Finite Element Analysis (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper reports simulation of a shape-memory-alloy (SMA) nitinol type active stent for wireless revascularization. The device comprises an inductive helical stent as an inductive component and a capacitive pressure sensor as a capacitive component. When the stent is coupled to an external coil with a radiofrequency (RF) signal, the stent can be expanded wirelessly by matching the signal with the device resonant frequency. By this approach, restenosis in a stented vessel can be potentially eliminated without a repeat stenting procedure.  However, the calculation of important parameters is difficult using the conventional analytical method due to the unconventional structure of the helical stent which can be considered an irregular solenoid. In this work, finite element analysis (FEA) was performed using ANSYS HFSS to simulate the inductance, quality factor, and series resistance of the device at the initial crimped state and expanded state as a function of frequency.